Propagation Behavior of Love-Type Waves in a Poro-elastic Medium using Staggered Grid Finite Difference Scheme - Jayantika Pal; Anjana Ghorai (Mechanics of Advanced Composite Structures)
The analysis of the propagation behaviour of seismic waves in porous medium requires a mathematical backup. That is pictured here. The present study investigates the propagation behavior of Love-type waves in a poro-elastic medium. A staggered grid finite-difference (SFD) scheme in time-space domain formulation for Biot’s equation of poro-elasticity is presented and applied to the problem. Complete theoretical seismograms for the horizontal and vertical components of displacement are obtained. The dispersion curves are evaluated considering the material parameters of different models. The stability analysis of the above numerical scheme is deliberated. From different graphs, it is noticed that there is a difference in phase velocity for various models. By observing the behaviour of the curve, we can understand the nature of the composite structure.  Our outcomes also endorse that finite-difference modeling is an important numerical tool to acquire knowledge about the transmission of seismic waves in a porous medium. The agreement is excellent.